Design of an echo canceller for acoustic halls - Akin, Ilke Levent (1993)
A major problem in many public address systems of large halls is the poor perception of message due to multiple reflections-echoes-in the hall. The general approach to this problem is to identify the characteristics of the echo path and then generate an echo replica which cancels out the real echo signal. In this thesis, a novel structured FIR equalizer is proposed for the cancellation process. It requires less taps than the existing equalizers and operates directly on the dominant echoes to generate an efficient echo replica. Extensive simulation studies are carried out for evaluating the performance of the proposed acoustic echo canceller. The new approach considerably improves the computational complexity and enables possible implementations on commercial DSP boards.